Nematoda Patogen Serangga Heterorhabditis spp. Untuk Pengendalian Hama Penggerek Batang Lada - Indriati, Gusti; Trisawa, Iwa Mara (Pusat Penelitian dan Pengembangan Perkebunan, 2011)
The research aimed to get control technology of L. piperis with entomophatogenic nematodes Heterorhabditis spp. Completely randomized design was used with 5 treatment and 3 replication. Research was conducted in the laboratory of Balittri and Sukamulya Experimental Station at West Java,Â from January to December 2010. The result showed that the utilization of entomophatogenic nematodes HeterorhabditisÂ spp. can kill the larvae of L. piperis 61.24 % but in adult stage had not show the effectiveness yet.